2017
DOI: 10.1111/trf.14050
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model for estimating residual transmission risk of occult hepatitis B virus infection with different blood safety scenarios

Abstract: The model can be used to compare different screening and/or PI strategies in reducing viral transmission risk and could serve as a tool in evaluating efficacy of alternative blood safety scenarios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(69 citation statements)
references
References 21 publications
5
60
0
4
Order By: Relevance
“…It is comparable to other South African studies that have reported OBI ranging from 8% to 18% in HIV coinfected patients . Our prevalence, however, is higher than the mathematical estimation computed by the South African Blood Transfusion services, which estimates that approximately 3.3% to 8.7% of OBI is missed in blood donors depending on the screening methods used …”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It is comparable to other South African studies that have reported OBI ranging from 8% to 18% in HIV coinfected patients . Our prevalence, however, is higher than the mathematical estimation computed by the South African Blood Transfusion services, which estimates that approximately 3.3% to 8.7% of OBI is missed in blood donors depending on the screening methods used …”
Section: Discussionsupporting
confidence: 72%
“…Transfusion services, which estimates that approximately 3.3% to 8.7% of OBI is missed in blood donors depending on the screening methods used. 32 The prevalence of HBV in dialysis patients varies and correlates with the endemicity in the general population of the region. 33 Based on HBsAg positivity, rates among dialysis patients are reported to be 0.9% in the USA, 10.0% in Brazil, and 16.8% in Taiwan, which correspond to the background prevalence of HBV in these regions.…”
Section: Discussionmentioning
confidence: 99%
“…The model developed by Weusten and colleagues predicted that 14% of residual HBV transmission would originate from NAT negative units 18. This prediction is supported by limited data from a Japanese look-back study that found 7/43 possible OBI TTI associated with donations confirmed NAT negative 11.…”
Section: Discussionmentioning
confidence: 95%
“…Despite progress in donor screening and laboratory testing, a small risk of bacterial, viral, or protozoal contamination of PLTs persists. There is also a continuous risk from newly emerging blood transfusion–transmitted infectious agents .…”
Section: Discussionmentioning
confidence: 99%